All-Epiphyseal Physeal-Sparing Anterior Cruciate Ligament Reconstructive Surgery: A Study of 3-Dimensional Modeling to Characterize a Safe and Reproducible Surgical Approach - Daniel A. Marchwiany, M.D; Cody Lee, M.D; Philip Ghobrial, B.S; Richard Lawley, M.D; Steven C. Chudik, M.D (Elsevier, 2020)
Purpose: The purpose of this study was to use 3-dimensional magnetic resonance imaging modeling of the skeletally immature knee to help characterize safe and reproducible tunnel positions, diameters, lengths, trajectories, and distances from anatomic landmarks and the physeal and articular cartilage for physeal-sparing anterior cruciate ligament (ACL) reconstructive surgery. Methods: Magnetic resonance imaging from 19 skeletally immature knees with normal anatomy were gathered. The 3-dimensional models were created, and the relevant anatomic structures were identified. Cylinders simulating tunnel length, diameter and trajectory were superimposed onto the models, and descriptive measurements were performed. Results: A safe position for the creation of an 8 mm diameter femoral tunnel was described in the lateral femoral condyle. The femoral tunnel length averaged 25.5 ± 2.6 mm. The bony entry point was located 3.8 ± 2.4 mm proximally and 12.7 ± 2.2 mm posteriorly to the lateral epicondyle. The shortest distance from the tunnel edge to the physis and femoral articular cartilage was 2.8 ± 0.7 mm and 3.7 ± 0.9 mm, respectively. The safe position for an 8 mm diameter tibial tunnel was also identified and described in the proximal tibia. The epiphyseal tibial tunnel length from the ACL footprint to the physis averaged 15.5 ± 1.6 mm. The proximal tibial epiphysis was found to accommodate a tibial crosspin measuring 63.5 ± 5.9 mm in length and 8.2 ± 1.5 mm in diameter without disrupting the physis or articular cartilage. Conclusions: Three-dimensional modeling created from magnetic resonance imaging can help define important anatomic relationships for physeal-sparing ACL reconstructive surgery in skeletally immature knees and may assist in reducing the risk of injury to local anatomic structures. Clinical Relevance: Knowledge of the anatomic relationships in skeletally immature knees serves as a valuable reference for surgeons performing physeal-sparing ACL reconstruction surgery.